2021
DOI: 10.3390/en14164927
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Beef Drying Process in a Heat Pump Chamber Dryer

Abstract: Uneven air distribution in chamber dryers is a common and serious technological challenge. A study using CFD (Computer Fluid Dynamics) simulation, supported by measurements in a heat pump chamber dryer, confirmed irregular airflows. Performing simulations with modified settings and additional chamber modifications enabled the airflows to be visualized and optimized. It was shown that a modification of the chamber where a rotating disc had been used had a positive effect on the uniform distribution of air flows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Liao et al [ 14 ] proposed an MSR-RBF-ARX model for drum tobacco dryer to simulate the drying characteristics of tobacco particles, and found that the contact part between the inner wall of the tower and the outlet end was in an outward form, which was conducive to improving the uniformity of the outlet water, but the overlap of the orifice plates did not affect the uniformity of the outlet water. Olejnik et al [ 15 ] simulated the drying chamber, realized the visualization and optimization of air flow in the drying chamber, and modified the tower air flow dryer by using a rotating disc installed at the bottom of the drying zone, so that the air flow distribution in the dryer was more uniform.…”
Section: Introductionmentioning
confidence: 99%
“…Liao et al [ 14 ] proposed an MSR-RBF-ARX model for drum tobacco dryer to simulate the drying characteristics of tobacco particles, and found that the contact part between the inner wall of the tower and the outlet end was in an outward form, which was conducive to improving the uniformity of the outlet water, but the overlap of the orifice plates did not affect the uniformity of the outlet water. Olejnik et al [ 15 ] simulated the drying chamber, realized the visualization and optimization of air flow in the drying chamber, and modified the tower air flow dryer by using a rotating disc installed at the bottom of the drying zone, so that the air flow distribution in the dryer was more uniform.…”
Section: Introductionmentioning
confidence: 99%
“…To solve the problem, numerous investigations have been carried out to achieve an even temperature distribution in the barn. In this regard, different algorithms and analytical methods have been proposed [7][8][9][10]. Recently, replacing coal with methanol and biomass has become a research hot spot [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It uses three stainless steel cylinders with a circular nested form that has the advantage of uniform air flow and prevents the spread of lightweight samples over a drying system. Olejnik [12] found that a modification of the chamber where a rotating disc had been used had a positive effect on the uniform distribution of air flows in the drying chamber. Luo [13] used air-deflectors on the drying chamber's internal sidewalls to enhance the heat and mass transfer between the conveyor sludge and circulating airflow.…”
Section: Introductionmentioning
confidence: 99%